Analisis Fungsi Badan Permusyawaratan Desa (BPD) Dalam Penyelenggaraan Pemerintahan Di Desa Setren Kecamatan Slogohimo Kabupaten Wonogiri - Prasetiyo, Joko, Dra. Hj. Sri Arfiah, SH.M.Pd (2016)
This study aims to describe the function of the Consultative Body of the village (BPD) in the conduct of the Government in the village of the subdistrict Setren Slogohimo Wonogiri Regency. The research results expected contributed knowledge and information to the public about the functions of the Consultative Body of the village (BPD) in discussingthe draft rules agreed and shared village village chief, holding and disbursing the aspirations of the community of the village, and monitor the performance of the Organization of the Government of the village chief in the village. This type of research including qualitative research carried out in the field (field research). This research was carried out at the village and subdistrict Setren Slogohimo Wonogiri Regency. The resource person or informants in this study was the Chairman of the BPD Village Setren, members of BPD Setren Village, the village head, village community Setren Setren. Data analysis in research using the interactive model. The research results of the Agency's Consultative function analysis of village (BPD in discussing and agree on the draft regulation of the village along the village head, accommodate and channeling the aspirationsof the community of the village, and monitor the performance of the Organization of the village chief of Government in the village suggest that BPD Setren Village with the village chief Setren have discussed and agreed on three regulations that is, income and Budget Shopping Village (APBDes), Regulation No. 4 Setren Village in 2011 about the preservation of the environment. , The Draft Medium-Term DevelopmentOf The Village (RPJMDes). Execution of function of the BPD Setren Village in accommodating and channeling the aspirations of society still has not been fullest said this is because the constraints experienced by BPD Setren Village. The implementation of supervisory function carried out by the BPD Setren Village associated with the conduct of the Affairs of the Government and against the village chief in the village of APBDes and regulation menjalanjan, BPD Setren Village not only controlat the time of formation, and the determination of the APBDesa, but also APBDesa at the time it was implemented, and accounted for in the report of accountability for end of the year the village chief Setren to BPD Setren Village. Implementation of the Agency's consultative Function of the village (BPD) in the conduct of the Government in the village of the subdistrictSetren Slogohimo Wonogiri Regency have already done quite well buthave not been fullest because still there are constraints that can not be overcome by BPD Setren Village.